2021
DOI: 10.3390/molecules26164732
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Isolated Compounds from the Leaves of Combretum erythrophyllum (Burch.) Sond. and Withania somnifera (L.) Dunal against Fusarium Pathogens

Abstract: Crop diseases caused by Fusarium pathogens, among other microorganisms, threaten crop production in both commercial and smallholder farming. There are increasing concerns about the use of conventional synthetic fungicides due to fungal resistance and the associated negative effects of these chemicals on human health, livestock and the environment. This leads to the search for alternative fungicides from nature, especially from plants. The objectives of this study were to characterize isolated compounds from Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This fact could be attributed to the potential antifungal activity of some withanolide derivatives that are soluble in water. Thus, Seepe et al [ 66 ] reported that a withaferin A glycoside isolated from a Whitania species was active against Fusarium verticilloides.…”
Section: Resultsmentioning
confidence: 99%
“…This fact could be attributed to the potential antifungal activity of some withanolide derivatives that are soluble in water. Thus, Seepe et al [ 66 ] reported that a withaferin A glycoside isolated from a Whitania species was active against Fusarium verticilloides.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, selenium nanoparticles (SeNPs) synthesized by Lactobacillus acidophilus ML14 controlled F. culmorum and F. graminearum growth based on their powerful antioxidant and antifungal activities and hence, counteracting drought and heat stress in wheat plant [ 40 ]. Flavonoid, 5-hydroxy-7,4′-dimethoxyflavone which was extracted from Combretum erythrophyllum leaves using solvent acetone, inhibited the growth of many Fusarium species including F. graminearum with a MIC value of 0.63 mg/mL [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…After adding the inoculating agent, the randomly selected wheat heads were covered with a plastic bag, which has been removed after 24 h. The plants were then kept for one month before harvesting. All wheat seeds were collected (1.5 g/one wheat head) and ground using a coffee mill (Krups KM75 Coffee Grinder) as described before [ 41 ] and stored in the refrigerator.…”
Section: Methodsmentioning
confidence: 99%
“…A silica gel column was used to separate and purify the fractions as outlined by Seepe et al. [ 43 ]. The column was eluted with 100% petroleum ether as solvent and thereafter, 50 mL of mobile phase mixtures (v/v): petroleum ether: ethyl acetate and ethyl acetate: methanol at different solvent ratio.…”
Section: Methodsmentioning
confidence: 99%